Uji Validitas dan Reliabilitas Alat Ukur Kepuasan Pelanggan Pengguna Tiktok - Sardiyono, Annisa Aprilia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The internet as part of technological advancements that are considered to have the most influence on human dynamics in the current digital era, from the latest We Are Social report, it is stated that internet users in Indonesia continue to increase from year to year. It is noted that the demographics of users aged 16-64 years who use social media the most and will continue to increase every month are the Tiktok application. The initial function of the Tiktok application is to publish short videos. The method used in this study is linear regression analysis with a quantitative approach. The sample in this study amounted to 100 respondents selected using purposive sampling techniques. that buyer satisfaction through TikTok has a positive and significant effect on repurchase intentions. High buyer satisfaction will make the buyer have the intention to return to the same object compared to making purchases from other service providers or products in the same industry. In other words, when users or customers feel satisfied within themselves when using the services provided by the company, it will create an intention within the customer.